Status of Abandoned Children: A Comparative Study of Islamic and Pakistani Law - Abbasi, Ambreen; Mudasra Sabreen (Journal of Islamic and Religious Studies, 2019)
This paper deals with the rights of abandoned children in the context of Pakistani society. The main issue is regarding legal status of such children which results in violation of their rights. Islamic law provides for rules for abandoned children which can be provided as a source for legislation in Pakistan. The paper argues that there is a need to formulate a clear legislation to ensure rights and protection of abandoned children. Currently the laws enacted in Pakistan lack provisions related to abandoned children. On the one hand the solutions like adoption/kafalah should be channelized and regularized and on the other hand serious efforts should be made to create awareness regarding rights of abandoned children among the masses. This is a comparative study which discusses and analyses relevant provisions in Islamic as well as Pakistani law.